2022
DOI: 10.51847/kvdmoxw5gj
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Myasthenia Gravis Subgroups and its influence on Pregnancy and their Treatment Advances

Abstract: Antibodies that attack the neuromuscular junction induce myasthenia gravis, an immunological illness. Such antibodies assault and degrade postsynaptic molecules in by binding to the postsynaptic muscular end-plate. As a consequence, signal transduction is disrupted, resulting in muscular weakness and fatigability. Developments in our knowledge of the immunological mechanisms that cause myasthenia gravis have paved the way for the development of new targeted immunity treatments. The majority of myasthenia gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…It is advised that in the absence of refrigerators, insulin should be kept in a dark place with no humidity, moisture, and minimum or no exposure to direct heat sources or sun rays. [ 11 ] Based on this, several traditional and unconventional methods of insulin storage have been developed and are used in different countries, such as India, Tanzania, Sudan, Pakistan, Mali, Ethiopia, and Haiti. [ 3 ] Clay pots filled with water for evaporative cooling to store insulin are most commonly used by thousands of families in resource-limited countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is advised that in the absence of refrigerators, insulin should be kept in a dark place with no humidity, moisture, and minimum or no exposure to direct heat sources or sun rays. [ 11 ] Based on this, several traditional and unconventional methods of insulin storage have been developed and are used in different countries, such as India, Tanzania, Sudan, Pakistan, Mali, Ethiopia, and Haiti. [ 3 ] Clay pots filled with water for evaporative cooling to store insulin are most commonly used by thousands of families in resource-limited countries.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Clay pots filled with water for evaporative cooling to store insulin are most commonly used by thousands of families in resource-limited countries. [ 11 ] The different variants of unconventional methods of insulin storage include pot-in–pot refrigerators or the Zeer pot, mud pots, goat skin pots filled with water,[ 11 ] vegetable gourds filled with water, and buckets filled with wet sand. [ 3 ] It has been observed that the temperatures achieved by these devices are at or near room temperature, even in hot climates.…”
Section: Discussionmentioning
confidence: 99%